PENERAPAN MODEL PBL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Nabiilah Okti Salsabila; Alif Luthvi Azizah; Hariyanto; Ulwan Syafrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research is the low critical thinking ability of students in Civic Education learning for grade V at SD Negeri 10 Metro Timur. The purpose of this study is to see whether the application of the problem based learning model can improve students' critical thinking skills in Civic Education learning and to determine the differences in improving students' critical thinking skills with the PBL model and the inquiry model in Civic Education learning. This type of research uses a quantitative approach with a quasi-experimental method in the form of a non-equivalent control group design. The population in this study were all grade V students of SD Negeri 10 Metro Timur, totaling 51 students. Sampling used a purposive sampling technique, with class VA students as the experimental class and class VB students as the control class. Data collection techniques were carried out through tests and observations. Data analysis used in this study were the N-gain test and the t-test. The results of the data analysis using the N-gain test for the experimental class were 0.4 and the control class 0.3 with a difference of 0.1. Furthermore, the results of the data analysis using the t-test showed that the value = 2.495 with a value of 0.016 < 0.05. The conclusion of this study is that the application of the PBL model can improve students' critical thinking skills in Civic Education learning and there is a difference in improving students' critical thinking skills when the PBL model and the inquiry model are applied.